Pilar-Pilar Tata Ruang Lokal: Studi Kasus Parangtritis - Sudaryono Sudaryono (Journal of Regional and City Planning, 2007)
After years of experiences, to day we witnesses that the practices of decentralization concept tend to be far away from its main concepts: that is to strengthen hen and develop local values through people involvement in the development process. In the names of local needs, initiatives and power, decentralization today is used as a vehicle for exploiting local resources at all cost. Destruction of traditional and vernacular spaces and territory is one of most tangible fact that we could ¡dent ij5' as' the failure of implementation of the decentralization concept. This research aims to explore and develop concepts that could be used as an opposition approach for understanding the recent practices of decentralization. The exploration is focused on what this research called as "ruang lokal/local space and territory ". The research concludes that "local s1ac and territory" should be strengthen through its three pillars: (1) spatial compound (pelapisan spasial), meaning the engagement of space, human activities, and local values, (2) typology and structure of powers, to include: spiritual, cultural, institution, kinship, and economical powers, and (3) the character of local space and territory, which appears as a product of engagement of spatial capital and social capital.